Scalable and physiologically relevant microenvironments for human pluripotent stem cell expansion and differentiation. (1st February 2018) - Li, Qiang; Lin, Haishuang; Du, Qian; Liu, Kan; Wang, Ou; Evans, Catelyn; Christian, Hannah; Zhang, Chi; Lei, Yuguo
Abstract: Human pluripotent stem cells (hPSCs) are required in large numbers for various biomedical applications. However, the scalable and cost-effective culturing of high quality hPSCs and their derivatives remains very challenging. Here, we report a novel and physiologically relevant 3D culture system (called the AlgTube cell culture system) for hPSC expansion and differentiation. With this system, cells are processed into and cultured in microscale alginate hydrogel tubes that are suspended in the cell culture medium in a culture vessel. The hydrogel tubes protect cells from hydrodynamic stresses in the culture vessel and limit the cell mass smaller than 400 μ m in diameter to ensure efficient mass transport, creating cell-friendly microenvironments for growing cells. This system is simple, scalable, highly efficient, defined and compatible with the current good manufacturing practices. Under optimized culture conditions, the AlgTubes enabled long-term culture of hPSCs (>10 passages, >50 days) with high cell viability, high growth rate (1000-fold expansion over 10 days per passage), high purity (>95% Oct4+) and high yield (5.0 × 10 8 cells ml −1 ), all of which offer considerable advantages compared to current approaches. Moreover, the AlgTubes enabled directed differentiation of hPSCs into various tissue cells. This system can be readily scaled to support research from basic biological study to clinical development and the future industry-scale production.